Studi Eksplanatori Dan Konfirmatori Nasehat Rasul Paulus Tentang Kedewasaan Penuh Berdasarkan Efesus 4 :1 – 32 Di Kalangan Guru Pendidikan Agama Kristen Sekolah Dasar ( SD ) Se – Kota Surakarta - Thomas Prajnamitra; Hana Suparti; Sri Wahyuni; Paulus Sentot Purwoko (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2020)
This article is the result of a dissertation research which begins with an explanation of the Apostle Paul's Advice on Full Maturity based on the Book of Ephesians 4: 1 - 32 considering that Christian elementary school Christian education teachers in the city of Surakarta are indeed required to have full maturity because based on an initial survey questionnaire distributed to 25 elementary school Christian religious education teachers randomly in 5 sub-districts in Surakarta gave an indication that there are still elementary school Christian Religious Education teachers in Surakarta who have not been able to be role models for their students in showing the maturity of a teacher. The methodology used in this study is a quantitative method using a questionnaire and literature review. The results showed the level of implementation of the Apostle Paul's Advice on Full Maturity based on the Book of Ephesians 4: 1 - 32 in the medium category, the dominant dimension was growing in all things towards Christ (D3), and the dominant background was the length of time he was a teacher (L4).